The socio political demography of happiness - Sam Peltzman (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
Since 1972 the General Social Survey (GSS) has asked a representative sample of US adults "[are] you very happy, pretty happy, or not too happy?" Overall, the population is reasonably happy even after a mild recent decline. I focus on differences along standard socio demographic dimensions: age, race, gender, education, marital status income and geography. I also explore political and social differences. Being married is the most important differentiator with a 30-percentage point happy-unhappy gap over the unmarried. Income is also important, but Easterlin's (1974) paradox applies: the rich are much happier than the poor at any moment, but income growth doesn't matter. Education and racial differences are also consequential, though the black-white gap has narrowed substantially. Geographic, gender and age differences have been relatively unimportant, though old-age unhappiness may be emerging. Conservatives are distinctly happier than liberals as are people who trust others or the Federal government. All above differences survive control for other differences.
Keywords: D10; D60; E01; I31; J10; J12; J18; Z13; 330; happiness; demographics; family; Easterlin paradox; education; income; social capital; political ideology